Experiences with the Veterans’ Choice Program - Stroupe, Kevin T. (J Gen Intern Med, 2019)
BACKGROUND: To address concerns about Veterans’ access to care at US Department of Veterans Affairs (VA) healthcare facilities, the Veterans Access, Choice, and Accountability Act was enacted to facilitate Veterans’ access to care in non-VA settings, resulting in the “Veterans Choice Program” (VCP). OBJECTIVES: To assess the characteristics of Veterans who used or planned to use the VCP, reasons for using or planning to use the VCP, and experiences with the VCP. DESIGN: Mixed-methods. SUBJECTS: After sampling Veterans in the Midwest census region receiving care at VA healthcare facilities, we included 4521 Veterans in the analyses. Of these, 60 Veterans participated in semi-structured qualitative interviews. APPROACH: Quantitative data were derived from VA’s administrative and clinical data and a survey of Veterans including Veteran characteristics and self-reported use of VCP. Associations between Veterans’ characteristics and use or planned use of the VCP were assessed using logistic regression analysis. Interview data were analyzed using thematic analysis. KEY RESULTS: Veterans with a higher odds of reporting use or intended use of the VCP were women, lived further distances from VA facilities, or had worse health status than other Veterans (P ≤ 0.01). Key themes included positive experiences with the VCP (timeliness of care, location of care, access to services, scheduling improvements, and coverage of services), and negative experiences with the VCP (complicated scheduling processes, inconveniently located appointments, delays securing appointments, billing confusion, and communication breakdowns). DISCUSSION: Our findings suggest that Veterans value access to care close to their home and care that addresses the needs of women and Veterans with poor health status. The Mission Act was passed in June 2018 to restructure the VCP and consolidate community care into a single program, continuing VA’s commitment to support access to community care into the future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05224-y) contains supplementary material, which is available to authorized users.